Diffusional kurtosis imaging of parotid glands in Sjögren's syndrome: Initial findings. Issue 5 (21st March 2017) - Chu, Chen; Zhang, Huayong; Zhou, Nan; Dou, Xin; Li, Ming; Liu, Song; Zhu, Yun; Wang, Chun; Chen, Weibo; Chan, Queenie; Sun, Lingyun; He, Jian; et al.
Abstract : Purpose: To explore the role of diffusion kurtosis imaging (DKI) of parotid glands in diagnosing Sjögren's syndrome (SS). Materials and Methods: A total of 40 patients with SS and 40 healthy volunteers underwent 3.0T magnetic resonance imaging (MRI) including DKI, which generated the apparent diffusion coefficient (ADC), corrected diffusion (D), and diffusional kurtosis (K) values. The MR nodular grade was determined on the basis of MR morphological findings. Results: The parotid ADC, D, and K values in patients with SS were significantly higher than those of healthy volunteers ( P  = 0.011, < 0.001, 0.022, respectively). The parotid ADC and D values in patients with SS of MR nodular grade 0 were significantly higher than those of healthy volunteers (all P < 0.001). The parotid D value showed an accuracy of 75.0% and 87.9% in diagnosing patients with SS and MR nodular grade 0, respectively. The parotid ADC and D values correlated negatively, while the K values correlated positively with the MR nodular grade significantly in patients with SS ( r  = −0.741, −0.605, 0.424, all P < 0.001). All parotid DKI parameters differed significantly among patients with SS at different MR nodular grades (all P < 0.001). Conclusion: Parotid DKI parameters hold great potential in diagnosing SS, especially in early‐stage SS without MR morphological changes. Level of Evidence: 2 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2017;46:1409–1417.